The Effectiveness of Omnichannel As A Digital Marketing Medium in The Economy After The Covid-19 Pandemic - Rahmayanti Mahardikaningtyas; Norman Akromudin (Publikasi Indonesia, 2024)
Omni channel is a support that provides the best experience for customers until they feel satisfied. In today's digital era, the omnichannel concept allows interaction between businesses and their customers through various platforms with integrated channels. Customers can easily access all business information through various channels such as physical stores, websites, mobile applications, and social media. Customer interaction is practical and fast. Having omni channels consistently will provide the best experience to customers where they remain coordinated, and even though they use any channel, customer needs are still met uniformly. Using several types of omnichannel in the current digital era, especially in the period after the COVID-19 pandemic, where there is a shift in customer spending patterns, of course, will make it easier for business owners to do marketing and decision-making related to the company, the effectiveness of using omnichannel in company management, especially those run by company leaders with specific genders, also affects in terms of innovation carried out company